G411(P) Does paeds rock? experiences of paediatric trainees in yorkshire and the humber. (May 2019) - Redman, M; Payne, F
Abstract : Aims: This project aims to explore the experiences of paediatric trainees in Health Education Yorkshire and the Humber (HEYH), in order to identify areas to improve the experience of paediatric trainees in Yorkshire, and to compare results to a similar survey undertaken in 2017. Methods: An electronic survey was circulated to HEYH paediatric trainees between 21 st June – 31 st July 2018. Results: New General Data Protection Regulation 1 rules posed a significant barrier for dissemination of the survey. Fifty-seven out of 366 (16%) trainees responded, compared to 25% in 2017. Fifty-six percent (n=32) were satisfied with paediatric training in HEYH, 23% (n=13) were neither satisfied nor dissatisfied, 21% (n=12) were dissatisfied or very dissatisfied. Three individuals identified team support as a positive factor contributing to job satisfaction, whereas 37 individuals listed a variety of negative factors including lack of access to training, rota gaps, service provision, and more. The mean score for morale was 2.7 (where 1=very poor and 5=very good). Similar to findings in 2017, 2 results showed poor adherence to contractual entitlements. Further improvements are required in areas such as monitoring, work schedules and exception reporting. Conclusion: Recommendations include: Adherence to contractual rights including, for those on the: 2002 contract monitoring 2016 contract accurate work schedules (including all mandatory work) personalisation of work schedules action exception reports within appropriate timelines–Adherence to the joint NHS Employers and BMA Code of Practice 3 and Good Rostering Guide 4 A new mechanism for communication between HEYH paediatric trainees Improve engagement with exception reporting To compare our local results with national paediatric training experiences References: 2018reform of EU data protection rules. European Commission . Available online at: https://ec.europa.eu/commission/priorities/justice-and-fundamental-rights/data-protection/2018-reform-eu-data-protection-rules_en [Accessed 06/08/18]. Payne F, Redman M. The new (2016) junior doctors contract: Experiences of Yorkshire-based paediatrics trainees . Poster presentation at: RCPCH Conference 2018; 2018 Mar 13; Glasgow, UK. Code of Practice. NHS Employers . Available online at: https://www.hee.nhs.uk/our-work/medical-recruitment/code-practice-medical-recruitment [Accessed 03/08/18]. Good Rostering Guide. NHS Employers . Available online at: https://www.nhsemployers.org/case-studies-and-resources/2018/05/good-rostering-guide [Accessed 03/08/18].Declaration of interest: Melody Redman sits on the BMA Junior Doctors Committee.